Comprehensive analysis and selection of high oleic peanut varieties in China: A study on agronomic, yield, and quality traits - Fangping Gong; Zhuo Li; Xiaojian Sun; Yi Fan; Yinghui Liu; Yurong Dang; Hao Li; Xingguo Zhang; Xingli Ma; Zhongfeng Li; Kai Zhao; Dongmei Yin (Oil Crop Science)
Peanut (Arachis hypogaea L.) is an important oil crop. Oleic acid is a major factor that determines the quality of peanuts. Therefore, the high oleic and high oleic to linoleic acid ratio are the target traits in an advanced peanut breeding program. This study provided an extensive evaluation of the genetic and physical characteristics as well as disease resistance of 220 high oleic peanut varieties in China. Notably, these varieties clustered into five major categories based on their traits. A majority of these varieties have been bred using interspecific hybridization or selected from mutants of self-crossed parents, with the main parent varieties being Kaixuan 016 and CTWE. Analysis of disease resistance showed that most high oleic peanut varieties could resist two or three diseases. However, those varieties with resistance to multiple diseases were relatively scarce. Moreover, some high oleic peanut varieties showed no disease resistance or inadequate testing. The results further indicate that the genetic basis for high oleic peanut breeding is insufficient, highlighting the need for its further development. Importantly, our findings lay a critical foundation for future high oleic peanut breeding and promote better understanding of the genetic and trait diversity offered by these varieties.